A Study Protocol for Persons With Neurological Diseases: Linking Rehabilitation Goals to the International Classification of Functioning, Disability and Health With a Focus on Assistive Technology for Cognition and Its Effects - Lindner, Helen; Buer, Nina (Frontiers in Rehabilitation Sciences, 2022)
Persons with neurological diseases often have some degree of cognitive impairment. They are in need of assistive technology for cognition (ATC) to compensate for cognitive impairments that affect their daily functioning. Goal setting in relation to cognitive deficits using ATC are common in clinical practice, and therapists often set several rehabilitation goals together with a patient. However, these rehabilitation goals are usually phrased differently, which limit the comparison of ATC and rehabilitation goals. It is thus valuable to link the goals to some standardized terminologies, such as the International Classification of Functioning, Disability and Health (ICF). Furthermore, goal achievement is seldom used to evaluate long-term effects of ATC in persons with neurological diseases and limited attention has been paid to the factors that predict goal achievement in using the ATC as cognitive support in persons with neurological diseases. The aim of the project is 3-fold. Firstly, we will use the ICF to link rehabilitation goals regarding the use of ATC in adults with neurological diseases. Secondly, we will evaluate effects of the ATC using goal achievement over a 5-year period. Thirdly, we will explore the variables that predict goal achievement in relation to the effects of ATC.